VARIATIONS IN THE MEANING OF THE EMOTIVE WORD "ANDIKO" IN KARO LANGUAGE: A SOCIOPRAGMATIC PERSPECTIVE - Br. Ginting, Dasa Oktaviani (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This study aims to describe the manifestation of the meaning of the emotive word "andiko" in a sociopragmatic perspective. The substantive data source is the speech spoken by Karo people in which there are manifestations of variations in the meaning of the emotive word "andiko". The research data is in the form of snippets of speech containing variations in the meaning of the emotive word "andiko". The substantive data source is the speech spoken by Karo people in which there are manifestations of variations in the meaning of the emotive word "andiko" and the word "andiko" contained in Karo turi-turin. The data collection method used is by using the listening method and the chap method. This study found eight manifestations of the meaning of the emotive word "andiko" viewed from a sociopragmatic perspective, namely 1) meaning to show affection, 2) meaning to show concern, 3) meaning to show surprise, 4) meaning to show defense, 5) meaning to show praise, 6) meaning to show gratitude, 7) meaning to show surprise, and 8) meaning to show sadness.